CPF schemes : education revised minimum sum basic and enhanced investment. - Ho, Chui Ing. (2013)
Central Provident Fund (CPF), which was set up on 1 July 1955, touches our lives in many ways. It ranges from the joy of having our own homes to enjoying a gracious retirement through CPF’s easy home ownership and Minimum Sum Scheme.